1991
DOI: 10.1007/bf02461553
|View full text |Cite
|
Sign up to set email alerts
|

The embedding problem for predistance matrices

Abstract: A fundamental problem in molecular biology is the determination of the conformation of macromolecules from NMR data. Several successful distance geometry programs have been developed for this purpose, for example DISGEO. A particularly difficult facet of these programs is the embedding problem, that is the problem of determining those conformations whose distances between atoms are nearest those measured by the NMR techniques. The embedding problem is the distance geometry equivalent of the multiple minima pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Nevertheless, as reported in Browne (1987), the algorithms based on this approach produce more accurate results. The same was reported in Glunt et al (1991) and their related papers. It seems that the most powerful algorithm based on this MDS approach is the one developed by Kearsley et al (1998).…”
supporting
confidence: 81%
“…Nevertheless, as reported in Browne (1987), the algorithms based on this approach produce more accurate results. The same was reported in Glunt et al (1991) and their related papers. It seems that the most powerful algorithm based on this MDS approach is the one developed by Kearsley et al (1998).…”
supporting
confidence: 81%
“…For the case when r = n -1, Gaffke and Mathar [9] and Glunt et al [11] developed algorithms which yield a global minimum of the Sstress function. Recently, Alfakih et al [1] have also considered to minimize the same error function by solving a positive semidefinite programming problem with a quadratic objective function.…”
Section: (Ij)esmentioning
confidence: 99%
“…Also, smoothing techniques by Moré and Wu [18] and Stochastic/perturbation approaches by Zou et al [25] have been applied to the S-stress function. We note that the differentiability of the S-stress function brings rich mathematical properties such as those developed in the literature [9,11,1]. It has been shown that the minimization of the S-stress function can be formulated as a convex minimization problem when r = n -1.…”
Section: (Ij)esmentioning
confidence: 99%
See 1 more Smart Citation
“…Browne proposed a method for computing s-stress based on Newton-Raphson root finding [47]. Glunt reports that the method by Browne converges to the global minimum of (25) in 90% of the test cases in his dataset 6 [48].…”
mentioning
confidence: 99%